STUDY OF INDUSTRIAL RELATIONS: LABOR UNION, WORK AGREEMENT AND BIPARTIT - Mr Haryono (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
The demonstration on May 1 was a sign of industrial relations problems. Therefore, all involved parties (Company, Labor Union, Bipartit and Governance) must enforce the rules of employment agreements as stipulated in the labor law. Explicitly, this study aims to describe and analyze the extent industrial relation has been built. The research approach uses qualitative methods, in this case the law study. The results of the study confirm: 1) The law as a legally has clearly regulated employment. 2) The company has not been optimal in carrying out the mandate of the law. 3) The function of the employee union has not been optimal as an employee representative. 4) Government functions are not yet real